THE INFLUENCE OF SELF-EFFICACY AND COMPENSATION ON THE PERFORMANCE OF FAMILY HOPE PROGRAMME ASSISTANTS WITH MOTIVATION AS A MEDIATING VARIABLE: - NOVIANTY.AR, SRI; Kornelius, Yoberth; Rossanty, Niluh Putu Evvy (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2024)
This research aims to test and analyse the effect of self-efficacy on the motivation of PKH assistants, the effect of compensation on the motivation of PKH assistants, the effect of motivation on the performance of PKH assistants, the effect of self-efficacy on the performance of PKH assistants, the effect of self-efficacy on the performance of PKH assistants mediated by motivation, and the effect of compensation on the performance of PKH assistants mediated by motivation  This type of research is quantitative research  Using descriptive analysis method and hypothesis testing using SEM-PLS with a sample of 41 respondents consisting of Family Hope Programme facilitators in Tojo Una-Una District  The results of the analysis show that (1) Self-efficacy has a positive and significant effect on the motivation of PKH assistants  (2) Compensation has a positive and significant effect on the motivation of PKH assistants  (3) Motivation has a positive and significant effect on the performance of PKH assistants  (4) Self-efficacy has a positive and significant effect on the performance of PKH assistants  (5) Compensation has a negative and insignificant effect on the performance of PKH assistants  (6) Self-efficacy has a positive and significant effect on the performance of PKH assistants mediated by motivation  (7) Compensation has a positive and significant effect on the performance of PKH facilitators mediated by motivation.